2021
DOI: 10.1161/circulationaha.120.053062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socioeconomic Status, Race and Ethnicity, and Geography on Prenatal Detection of Hypoplastic Left Heart Syndrome and Transposition of the Great Arteries

Abstract: Background: Prenatal detection (PND) has benefits for infants with hypoplastic left heart syndrome (HLHS) and transposition of the great arteries (TGA), but associations between sociodemographic and geographic factors with PND have not been sufficiently explored. This study evaluated whether socioeconomic quartile (SEQ), public insurance, race and ethnicity, rural residence, and distance of residence (distance and driving time from a cardiac surgical center) are associated with the PND or timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…In CHD, lower SES is associated with multiple medical disadvantages during fetal and perioperative care. These include lower fetal detection rates 65 resulting in higher neonatal mortality, 66 longer time until surgery, 67,68 fewer interventions with extracorporeal membrane oxygenation, 69 fewer catheterizations 68 , and poorer adherence to cardiological and neurodevelopmental follow-up appointments. [70][71][72][73] Further, SES emerges repeatedly as an important factor in short-and long-term cognitive development in CHD patients 21,22,68,[74][75][76] and its impact on the cognitive outcome increases with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…In CHD, lower SES is associated with multiple medical disadvantages during fetal and perioperative care. These include lower fetal detection rates 65 resulting in higher neonatal mortality, 66 longer time until surgery, 67,68 fewer interventions with extracorporeal membrane oxygenation, 69 fewer catheterizations 68 , and poorer adherence to cardiological and neurodevelopmental follow-up appointments. [70][71][72][73] Further, SES emerges repeatedly as an important factor in short-and long-term cognitive development in CHD patients 21,22,68,[74][75][76] and its impact on the cognitive outcome increases with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Studies have shown that families with a lower socioeconomic status (SES) are associated with lower rates of prenatal detection of congenital HD, which results in gaps in appropriate referrals (ie, access to care). 16 , 17 …”
Section: Population‐level Approachmentioning
confidence: 99%
“…Infants born into >75th percentile for census tract poverty level were more likely to live close to the birth hospital and be transferred. Prior studies, including a recently published review using a national Medicaid dataset, have linked poverty with a lower likelihood of prenatal diagnosis (Campbell et al, 2021; Hill, Block, Tanem, & Frommelt, 2015; Krishnan et al, 2021). Our study further supports these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is unknown if the link between poverty and transfer after delivery is related to a failure of prenatal diagnosis, challenges in planning for birth hospitalization or relocation, or if there are other patient‐related barriers preventing relocation of mothers in this situation. A recent multicenter analysis from the Fetal Heart Society Research Collaborative, including 1,171 patients with HLHS from 2012 to 2016, found prenatal diagnosis of the defect to be less likely among mothers experiencing poverty, Hispanic mothers, and mothers living in rural locations (Krishnan et al, 2021). Future research should attempt to confirm if prenatal relocation is also less likely in poorer populations, and if this difference is attributable to physician error, systemic bias related to socioeconomic status, insurance status, or patient choice due to other stressors such as the need for childcare for other children, unstable housing, or job insecurity.…”
Section: Discussionmentioning
confidence: 99%